Carey Young's Palais de Justice. Issue 2 (3rd July 2018) - Gaakeer, Jeanne; Herz, Ruth; Kee, Joan; Mulcahy, Linda; Pilcher, Jeremy; Watt, Gary; Young, Carey
ABSTRACT: The symposium for this issue comprises six responses to the video artwork Palais de Justice (2017) by artist Carey Young. The video presents a study of the life of Brussels' vast, late-nineteenth-century court building. In Palais de Justice, Young presents 'a legal system seemingly centered on, and perhaps controlled by women'. The respondents are Jeanne Gaakeer, Ruth Herz, Joan Kee, Linda Mulcahy, Jeremy Pilcher and Gary Watt. Jeanne Gaakeer and Ruth Herz have the distinction of being, not only internationally respected scholars, but also experienced judges. Jeanne Gaakeer is a judge practicing in the Netherlands and Ruth Herz was formerly a judge in Germany. The six responses are followed by the artist's own reflections on her artwork and her response to the commentators' responses. Joan Kee writes that 'Young highlights access as a key entry point for thinking about the law. Who can avail themselves of the law? Who may enter (or exit) the courts? Who is excluded and by whose authority? The surreptitious looking and peering that define the experience of watching the film suggests how these questions deny ready answers'.